Analisis Pengaruh Pendapatan Asli Desa (Padesa), Dana Desa (Dd), Alokasi Dana Desa (Add), Dan Bagi Hasil Pajak Dan Retribusi Terhadap Belanja Desa Bidang Pendidikan(Studi Empiris Di Desa-Desa Se-Kabupaten Sukoharjo) - Habibah, Ummu, Andy Dwi Bayu Bawono, S.E., M.Si., Ph.D (2017)
This research aims to examine the influence of the Village local revenue (PADesa), Village funds (DD), Village Fund Allocation (ADD), and Profit sharing of tax and retribution (BHPR) on the village expenditures in education in 2016. The research uses population from all village in Sukoharjo district and purposive as a sampling model. The hyphothesis was tested by using multiple regression analysis with the coefficient of determination, f-tets and t-tests. The result shows that coefficient of determination gained 0,051 points. It means that 5,1 % variabel variant of village expenditures in education can be explained by PADesa, DD, ADD, and BHPR, meanwhile the rest of 94,9 % was explained by other factors. The simultant test result shows that PADesa, DD, ADD, and BHPR significally influence to village expenditures in education. However, in partial, research shows that PADesa, ADD, and BHPR is not significally influence to village expenditures in education, only DD has significally influence to the village expenditures in education